Effectiveness and safety of ultrasound-guided high-intensity focused ultrasound ablation for the treatment of colorectal cancer liver metastases. (31st December 2022) - Yang, Tong; Chen, Qian; Kuang, Lanqiong; Fu, Zhongxiang; Wang, Yiran; Chen, Yu; Yang, Lixia; Xu, Yonghua
Abstract: Objective: To investigate the effectiveness and safety of high-intensity focused ultrasound (HIFU) ablation for patients with colorectal liver metastases (CRLMs) who were unsuitable for hepatectomy. Methods: This is a multicenter retrospective study. 238 CRLM patients underwent ultrasound-guided HIFU (USgHIFU) ablation in three medical centers from October 2014 to December 2020. Patients who had complete colorectal cancer resection, but exhibited extra-hepatic metastasis were excluded from this study. HIFU ablation procedure was performed, and contrast-enhanced MR imaging and/or contrast-enhanced CT examinations were conducted and mRECIST was used for the assessment of tumor ablation effectiveness before and after treatment, and every 3 months thereafter. Adverse events and complications were recorded. Results: 43 CRML patients (27 male, 16 female, aged 29–82 years) were enrolled and underwent a USgHIFU ablation procedure. CR (complete response) was achieved in 21 patients, while PR (partial response) was observed in 21 patients and SD (stable disease) was achieved in one patient, respectively. The objective response rate was 97.7%. Median OS (overall survival) was estimated to be 31 months, and1-year and 18-month overall survival was 90.7% (39/43) and 72.1% (31/43), respectively. For CR and PR patients, the median OS was 35 months and 23 months, respectively ( p = 0.00). The majority of adverse events were pain in 22 cases (51.2%) and local skin edema in 33 cases (76.7%). No severe adverse events or complications were reported and recorded. Conclusions: USgHIFU ablation is a safe and effective treatment option for CRLM patients, especially for patients who are unsuitable for hepatectomy.